Proceedings of the 3rd international workshop and congress on eMaintenance : June 17-18 Luleå, Sweden : eMaintenance, Trends in technologies & methodologies, challenges, possibilites and applications - Kumar, Uday; Karim, Ramin; Parida, Aditya; Tretten, Phillip (Luleå tekniska universitet, Drift, underhåll och akustik, 2014)
Compilation of papers presented in the technical sessions during the eMaintenance 2014. Godkänd; 2014; 20140611 (raka)